Educación musical y la expresión corporal en niños de cinco años de la Institución Educativa Inicial N°601491 Madre Teresa de Calcuta, San Juan 2024 - Torres Rojas, Maria Milagros (2024)
The objective of this research is to evaluate the relationship between musical education and body expression in five-year-old children of the Institución Educativa Inicial N°601491 Madre Teresa de Calcutta San Juan 2024. The study was conducted with a quantitative approach and, in particular, with a non experimental correlational research design. The studied population consisted of 100 children from the aforementioned educational institution. The observation technique was used, using an observation guide validated by three experts in the area to collect the data. The results obtained through the Spearman correlation coefficient test, with a value of r= 0.715 and a significance of sig. = 0.847, indicate a high relationship between musical education and corporal expression in children, thus rejecting the null hypothesis and accepting the main hypothesis. Consequently, it is concluded that there is a significant relationship between musical education and corporal expression in five-year-old children of the Initial Educational Institution N°601491 Madre Teresa de Calcuta San Juan 2024.